Measles. Issue 5 (September 2015) - Lindberg, Claire; Lanzi, Maria; Lindberg, Kristen
<x xml:space="preserve">Abstract</x> Abstract Measles (Rubeola), although considered eradicated in the United States, still causes periodic outbreaks. Vaccine refusal leads to vulnerable pockets of individuals who may become infected once the virus is imported from countries where it is endemic. In turn, these individuals may spread the virus to young infants and to other vulnerable individuals. Many healthcare providers are not familiar with this disease or with the factors that contribute to the risk of spread. Measles causes a serious febrile illness that may lead to pneumonia, blindness, deafness, neurological disorders, and even death. Patients with measles need supportive care and administration of oral vitamin A. The measles vaccine is highly effective and considered extremely safe, but misinformation about the safety of this and other vaccines has decreased immunization coverage in some areas of the country. Mandatory immunization laws exist in every state and have been upheld by courts including the United States Supreme Court, but laws and exemptions vary among states. Nurses can play a strong role in care of patients with measles, case identification, and prevention of transmission. Most importantly, because nurses hold positions of trust in their communities, they should be tireless frontline advocates for immunization. The purpose of this article is to provide information on measles, its transmission, signs and symptoms, treatment, prevention, and relevant laws and regulations.